PEMODELAN UML SISTEM PENDUKUNG KEPUTUSAN DALAM PENENTUAN KELAS SISWA SISWA TUNAGRAHITA - Ommi Alfina; Fitriana Harahap (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2019)
Class determination system for mentally retarded new students in SLB C Musdalifah is still done manually with several obstacles in the learning process. This is because there are no tests conducted on new students so that the handling of mental retardation student learning is a bit disrupted. Every mentally retarded child has different handling according to their individual abilities. This study aims to apply the modeling of UMI in designing the decision support system application in determining the class of mentally retarded children. UML is an Object Oriented (OO) based modeling concept that can help in system design and analysis. In UML many diagrams can be used to analyze systems and system design. UML has three main categories of diagrams namely structure diagrams, behavior diagrams and interaction diagrams. Where each of these categories has a diagram that explains the system architecture and integrated with each other.